2013
DOI: 10.2119/molmed.2013.00027
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Activates Augmenter of Liver Regeneration (ALR) via Antioxidant Response Element and Links Oxidative Stress to Liver Regeneration

Abstract: Liver regeneration can be impaired by permanent oxidative stress and activation of nuclear factor erythroid 2-related factor 2 (Nrf2), known to regulate the cellular antioxidant response, and has been shown to improve the process of liver regeneration. A variety of factors regulate hepatic tissue regeneration, among them augmenter of liver regeneration (ALR), attained great attention as being survival factors for the liver with proproliferative and antiapoptotic properties. Here we determined the Nrf2/ antioxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 51 publications
(64 reference statements)
2
55
0
Order By: Relevance
“…A similar property to that in ALR has been identified in yeast; knockouts of its homolog, ERV1, lead to the death of yeast . The ALR protein has been shown to be important for mitochondrial biogenesis and gene expression, protein import machinery of the mitochondria, checking oxidative stress, regeneration of liver, and maturation of liver progenitors …”
Section: Liver Physiology and Alrmentioning
confidence: 75%
“…A similar property to that in ALR has been identified in yeast; knockouts of its homolog, ERV1, lead to the death of yeast . The ALR protein has been shown to be important for mitochondrial biogenesis and gene expression, protein import machinery of the mitochondria, checking oxidative stress, regeneration of liver, and maturation of liver progenitors …”
Section: Liver Physiology and Alrmentioning
confidence: 75%
“…In addition to the well-documented role of Nrf2 in orchestrating adaptation to oxidative stress, increasing evidence indicates that Nrf2 also contributes to cell growth and the repair of damaged tissue [42][43][44][45]. In this case, activation of Nrf2 is presumed to facilitate cell growth by: (1) increasing nutrient availability; (2) augmenting the levels of NADPH, ATP and metabolic intermediates required for synthesis of macromolecules; (3) increasing production of signalling molecules; (4) limiting inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that Nrf2 pathway has been shown to regulate the cellular antioxidant response and improve the process of liver regeneration. It was shown that Nrf2/antioxidant response element (ARE) system is an effective way to control ALR expression necessary for hepatic regeneration [20]. Another study showed that ROS-induced Nrf2 is capable of triggering transcription of proteins that play vital role in cell redox homeostasis function [52].…”
Section: Pathways Linking Psychosocial Stress To Liver Regenerationmentioning
confidence: 99%
“…It has been reported that the absence of Nrf2 results in delayed liver regeneration after partial hepatectomy [54]. The Nrf2 regulates the expression of ALR which acts as antioxidative protein and plays an important role in liver regeneration to ensure the survival of the damaged cells [20]. Free Nrf2 translocate to the hepatic cell nucleus where it regulates the expression of several genes involved in cell proliferation (Fig.…”
Section: Stress-induced Gcs Affect Nuclear Factor Nrf2 During Liver Rmentioning
confidence: 99%
See 1 more Smart Citation